Clasificación de los géneros de gramíneas (Poaceae) mexicanas - Valdes Reyna, Jesus; Davila A., Patricia D. (Instituto de Ecología, A.C., 1995)
The grass family (Poaceae) is extremely well represented in Mexico, with six subfamilies, 26 tribes, 30 subtribes, 206 genera, and slightly more than 1,000 species. Of the 206 genera, twenty two are monotypic, eleven are endemic, 16 are dioecious, and 49 are introduced (naturalized or cultivated). The genera are presented in a system of phylogenetic classification.